The PI4K2A gene positively regulates lipid synthesis in bovine mammary epithelial cells and attenuates the inhibitory effect of t10,c12-CLA on lipid synthesis - Tong Mu; Honghong Hu; Xiaofang Feng; Chuanchuan Wang; Juan Zhang; Zhihong Sun; Yaling Gu (Scientific Reports)
Abstract Currently, the identification of valuable candidate genes affecting milk fat synthesis in dairy cows is still limited, and the specific regulatory mechanism is still unknown. In this study, we used primary bovine mammary epithelial cells(BMECs)as a model and utilized overexpression and knockdown techniques for the PI4K2A gene to investigate the specific mechanisms by which it regulates lipid metabolism in BMECs. We studied whether PI4K2A regulates the inhibition of trans-10, cis-12 conjugated linoleic acid (t10,c12-CLA) on lipid synthesis in BMECs. The results revealed that PI4K2A plays a crucial regulatory role within the cytoplasm of BMECs, positively impacting fatty acid (FA) transport, triacylglycerol (TAG) synthesis, and lipid droplet secretion (p < 0.05 for all effects). Furthermore, PI4K2A promotes cell proliferation and inhibits apoptosis (p < 0.05). This study also confirmed that overexpressing the PI4K2A gene can effectively reduce the inhibitory effect of t10,c12-CLA on lipid synthesis in BMECs. Our findings have deepened the understanding of the regulatory mechanisms of milk fat synthesis and provide potential genetic targets for the improvement of lactation traits in dairy cows.